Cleaner Production in the Marble Industry (Case Study: UD Warna Utama) - Aryndhy, Funny Gustanty; Suhardi, Bambang; Astuti, Rahmaniyah Dwi (Performa: Media Ilmiah Teknik Industri, 2000)
UD Warna Utama is one of the marble stone industries located in Tulungagung, East Java. In the marble stone process, there are three stages of production, namely the sawing of marble blocks, the sawing of marble slabs, and the polishing of marble. In the production process, the waste generated is sometimes sold as building foundation material, while other residues are directly disposed of into the surrounding environment of the factory, causing environmental pollution. This research aims to identify opportunities for improving efficiency and reducing environmental impact, as well as providing alternative proposals to minimize and utilize the waste generated in accordance with the concept of clean production. A quick analysis of the material flow using the Quick Scan method and interviews yielded several options for implementing clean production, namely the Recycle and Reuse methods. The proposed alternatives were evaluated using the B/C Ratio and Payback Period feasibility analysis, resulting in viable proposals for implementation, including the creation of water retention systems for block stone sawing processes, selling sludge waste as construction material, making mosaics, and producing terrazzo.